Use of Human Hair as a Potential Biomonitor for Zinc in the Pendik District Istanbul Turkey - (:unkn) unknown (ARS DOCENDI, 2009)
A sample of 70 high school students (aged 16 to 20) studied from the Pendik District Istanbul-Turkey in order to determine the levels of zinc in their hair. Levels of Zn were measured by using Varian AA200 model atomic absorption spectrometry. The student's personal data such as age, sex, location, general state of health, diet habits, possible use of pharmaceuticals, alcohol, coffee and tobacco, etc was considered and only healthy student's hair were used as experimental materials. The mean values of Zn in student's hair were measured as 216.19 +/- 16.50 ppm. The Zn values of six different station's soil samples in the Pendik District were, measured to compare with the hair Zn values. According to the results of our study, hair is a good biomonitor for Zn and can be used for diagnostic purposes, as indices body status in humans as well as for detecting certain diseases. Increasing Zn levels in hair could be a monitor for high traffic density while decreasing could be a monitor for industrial pollution. Additionally, higher or lower Zn in human hair could reflect firstly dietary habits, then sex, age, financial status, smoking habits and environmental status.
Keywords: Mineral elements; contaminants; intake; hair levels; biomonitor; zinc; SCALP HAIR; METAL CONCENTRATIONS; ORGANIC POLLUTANTS; CANCER-PATIENTS; ELEMENTS; SAMPLES; CADMIUM; TISSUES; COPPER; L.